Agonistic nanobodies and antibodies to human VISTA - Yu-Heng Vivian Ma; Amanda Sparkes; Ema Romão; Shrayasee Saha; Jean Gariépy (Taylor & Francis Group, 2021)
The V-domain Ig Suppressor of T-cell Activation (VISTA) is an immune checkpoint regulator that suppresses immune responses and is readily expressed on human and murine myeloid cells and T cells. This immunosuppressive pathway can be activated using VISTA agonists. Here, we report the development of murine anti-human VISTA (anti-hVISTA) monoclonal antibodies (mAbs), anti-hVISTA nanobodies (Nbs), and cross-reactive rat anti-murine/human VISTA (anti-hmVISTA) mAbs. All mAbs and Nbs generated bound to VISTA (human and/or murine) with dissociation constants in the sub-nanomolar or low nanomolar range. Competition analysis revealed that the selected Nbs bound the same or a nearby epitope(s) as the human VISTA-specific mAbs. However, the cross-reactive mAbs only partially competed with Nbs for binding to hVISTA. All mAbs and one Nb (hVISTANb7) were able to strongly detect VISTA expression on primary human monocytes. Importantly, the murine anti-hVISTA mAbs 7E12 and 7G5 displayed strong agonistic activity in human peripheral blood mononuclear cell cultures, while Nb7 and rat anti-hmVISTA mAbs 3C3, 7C6, 7C7, and 7G1 also behaved as hVISTA agonists, albeit to a lesser extent. Cross-reactive mAbs 7C7 and 7G1 further displayed agonistic potential in murine splenocyte assays. Importantly, mAb 7G1 significantly reduced inflammation associated with the murine model of imiquimod-induced psoriasis. These agonistic VISTA mAbs may represent therapeutic leads to treat inflammatory disorders.